Сomputer simulation of selective laser melting of fine-grained metallic powders - Gordeev, Georgy Andreevich; Krivilyov, Mikhail Dmitrievich; Ankudinov, Vladimir Evgenievich (Computational Continuum Mechanics, 2017)
A mathematical model of selective laser melting (SLM) of fine-grained metallic powders subjected to pulse laser annealing has been developed. The powder bed is considered in approximation of a continuous medium, where its effective thermophysical properties depend on local porosity. The model allows calculation of the unsteady distributions of temperature, specific enthalpy, local porosity, morphology and thickness of the track (layer) under study. In this paper, all stages of problem solving are described, including its mathematical formulation and numerical implementation. An important feature of the finite element model is the dependence of basic functions on the variable which characterizes the shrinkage of the powder bed. Thus, the finite element mesh requires regular control of quality and dynamic remeshing. Validation of the model is done through qualitative comparison with the SLM experiments performed at similar regimes. The effect of peak power density, pulse energy, and pulse duration on the quality of the track is studied to reveal governing parameters of SLM using Fe powder as a reference system. It is shown that an increase in pulse energy with increasing power density and pulse duration leads to better efficiency and quality of layer cohesion. At the same time, this positive effect decays at some critical parameters. This happens due to powder burning and intensifying of heat transfer to the substrate. It was shown that, at fixed pulse energy and effective beam radius, variation of power density and pulse duration keeps the roughness on the lateral faces of a 3D element.